(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Mosquitoes constitute a serious Public Health menace, resulting in millions of death worldwide each year. Emergence of insecticide resistant strains of the mosquitoes poses a serious threat and hence calls for alternative control measures. This study assessed the larvicidal efficacy of the methanolic leaf extract of Calotropis procera against the 3rd instar larvae of Culex quinquefasciatus, after ten generations for 24 hours of exposure. Larvicidal activities of the leaf of the plant were studied on laboratory reared larvae of Culex quinquefasciatus at concentration ranges of 15 mg/L to 19 mg/L. The LC50 values were obtained from Probit analysis at 95% confidence limit (CL). Results of the study indicated that the LC50 values obtained from the parent generation (F0) to the tenth generation (F10) were; 15.79 mg/L, 16.58 mg/L, 17.29 mg/L, 18.07 mg/L, 18.95 mg/L, 19.99 mg/L, 20.65 mg/L, 21.18 mg/L, 22.80 mg/L, 25.16 mg/L and 32.98 mg/L respectively at 24hours. A higher efficacy of activity was exhibited by the extract at the parent generation (F0) with lowest LC50 of 15.97 mg/L at 24h. The results of this research therefore underscore the efficacy of the plant and further suggest the use of the leaf extracts of Calotropis procera in the control of mosquito vectors and indirectly to the diseases they vectored.